Patterns in and predictors of stream and river macroinvertebrate genera and fish species richness across the conterminous USA - Hughes Robert M.; Herlihy Alan T.; Comeleo Randy; Peck David V.; Mitchell Richard M.; Paulsen Steven G. (Knowledge and Management of Aquatic Ecosystems, 2023)
Both native and non-native taxa richness patterns are useful for evaluating areas of greatest conservation concern. To determine those patterns, we analyzed fish and macroinvertebrate taxa richness data obtained at 3475 sites collected by the USEPA's National Rivers and Streams Assessment. We also determined which natural and anthropogenic variables best explained patterns in regional richness. Macroinvertebrate and fish richness increased with the number of sites sampled per region. Therefore, we determined residual taxa richness from the deviation of observed richness from predicted richness given the number of sites per region. Regional richness markedly exceeded average site richness for both macroinvertebrates and fish. Predictors of macroinvertebrate-genus and fish-species residual-regional richness differed. Air temperature was an important predictor in both cases but was positive for fish and negative for macroinvertebrates. Both natural and land use variables were significant predictors of regional richness. This study is the first to determine mean site and regional richness of both fish and aquatic macroinvertebrates across the conterminous USA, and the key anthropogenic drivers of regional richness. Thus, it offers important insights into regional USA biodiversity hotspots.